Optimal Timing of Delivery in Women with Higher Order Cesareans: A Cohort Study - Miller, Emily S.; Nielsen, Chloe; Zafman, Kelly B.; Fox, Nathan S. (American Journal of Perinatology, 2018)
Objective To evaluate whether a planned early term delivery or a planned 39-week delivery is associated with differences in perinatal outcomes in women undergoing a higher order cesarean (HOC).Study Design This cohort study included women with singleton gestations with a history of three or more prior cesareans who delivered at one of two urban tertiary care hospitals. One center routinely delivered HOC at 39 weeks' gestation and the other at 37 weeks. Maternal and neonatal morbidities were compared using bivariable and multivariable analyses.Results The policy of 37-week delivery was associated with a decrease in unscheduled deliveries (15.3 vs. 41.1%; p < 0.001). Planned delivery at 37 weeks was associated with a decreased incidence of composite maternal morbidity (1.6 vs. 7.9%; p = 0.002) and 5-minute Apgar score less than 7 (0.4 vs. 6.4%; p < 0.001), but these differences were not significant after controlling for potential confounders (adjusted odds ratio [aOR]: 0.30, 95% confidence interval [CI]: 0.08–1.17; aOR: 0.13, 95% CI: 0.01–1.30, respectively). There were no other differences in perinatal outcomes.Conclusion Compared with planned delivery at 39 weeks, a policy of planned delivery at 37 weeks was associated with a reduction in unscheduled deliveries, but there were no measured differences in perinatal outcomes.
Keywords: higher order cesarean; multiple cesareans; timing of delivery; obstetric complications